(3OQGSGJ GOGQjI aj GbJUGOjGJ GdeTQhY (B((3c(B12) /s - (3YThT, eMeO Gjef YHO GddWjas ((3GdbGgQI(B: s (3eWHYI eQcR GdJYdje GdeaJhM(B, s, 1993)
(3GbJUGOjGJ GdeTQhY GdLOjO, OQGSGJ GdLOhi GdeHOFjI, OQGSI GdLOhi GdJShjbjI, OQGSI GdLOhj GdeGdjI, Jbjje GdLOhiGdbhejI deTQhY GdGSJKeGQs
(3HHdjhZQGajG U(B.322s
Keywords: (3GdGSJKeGQs; (3GdeTQhYGJs